The Grass Is Not Greener on the Other Side: The Role of Attention in Voting Behaviour - Lucie Coufalová; Štěpán Mikula (Masaryk University, Faculty of Economics and Administration, 2022)
The effect of ranking and the effect of attention both increase the chances that candidates running in the top positions of electoral lists will win voters' support. We exploit a variation in ballot layout (the location of the break between the first and second sides of the ballot) in the 2006–2017 Czech parliamentary elections to disentangle these effects and identify the effect of attention. We show that being listed on the reverse side of the ballot paper decreases electoral support by at least 50 %.
Keywords: D72; D91; P16; 330; voting behavior; attention; preferential voting; Czech parliamentary elections